2015
DOI: 10.1016/j.ijcha.2015.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two dimensional quantitative coronary angiography (2D-QCA) with optical coherence tomography (OCT) in the assessment of coronary artery lesion dimensions

Abstract: ObjectivesThere is limited data on how well 2D-QCA and OCT agree with each other for measurement of coronary artery lumen dimensions. We aimed to assess the agreement between the two modalities.MethodsPatients undergoing OCT for assessment of coronary artery lesions were reviewed. Minimum luminal diameter (MLD), proximal reference diameter and distal reference diameter were measured for each lesion prior to stenting.ResultsOCT was performed in 64 patients and 40 lesions were suitable for analysis. There was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…FDOCT provided more accurate quantitative measurements than quantitative coronary angiography and intravascular ultrasound. The results of the current study were in line with the results of a multicenter prospective study ( 4 ), retrospective analyses ( 10 12 ), the phantom study ( 13 ), and a prospective study ( 14 ), but not in line with the OPINION trial ( 8 ) and the ILUMIEN III study ( 15 ). The reasons behind such discriminations of results are the gap between clinical trials and studies based on diagnostic performance in clinical practice ( 16 ).…”
Section: Discussionsupporting
confidence: 73%
“…FDOCT provided more accurate quantitative measurements than quantitative coronary angiography and intravascular ultrasound. The results of the current study were in line with the results of a multicenter prospective study ( 4 ), retrospective analyses ( 10 12 ), the phantom study ( 13 ), and a prospective study ( 14 ), but not in line with the OPINION trial ( 8 ) and the ILUMIEN III study ( 15 ). The reasons behind such discriminations of results are the gap between clinical trials and studies based on diagnostic performance in clinical practice ( 16 ).…”
Section: Discussionsupporting
confidence: 73%
“…These findings might guide physicians in deciding on stent‐ and postdilatation balloon sizing, and support the use of intravascular imaging in LMCA stenting []. Given the structural undersizing based on QCA, IVUS helps in correctly identifying the exact LMCA length and area and thereby improves outcomes of complex LMCA PCI []. More specifically, we demonstrated that 19% of the patients presented with IVUS derived mean luminal dimensions of >5 mm, requiring post dilatation with balloons up to 5 mm along with the use of stents with sufficient post dilatation margins.…”
Section: Discussionmentioning
confidence: 60%
“…6). As a complete match of measurements derived from different modalities is not feasible, our opinion is that MSCT can be used to assess the average area in coronary arteries treated with BRS [10,18,19]. Metallic markers could potentially introduce an artifact when calculating average lumen area, but in our study, this had little impact.…”
Section: Discussionmentioning
confidence: 79%